Sharpening the Concept of Tax Literacy as an Effort to Improve Tax Compliance - Jessy Tantriangela; Milla Sepliana Setyowati (Universitas Medan Area, 2023)
The self-assessment system used by many countries raises the issue of non-compliance in the taxation sector. With this, tax literacy is believed to be able to increase tax compliance. Unfortunately, studies that specifically study tax literacy are still rarely found. This article aims to sharpen the existing concept of tax literacy, especially in the context of raising tax compliance. This article uses a qualitative method, where the researcher summarizes and presents the condition of the knowledge of tax literacy to this day. In this article, the researcher sharpens three dimensions of tax literacy. First, tax literacy is related to the taxation knowledge of the taxpayers, namely general, procedural, and legal knowledge. Second, tax literacy is related to the taxpayers’ personal values, which is related to their interest in reading about taxation. Third, tax literacy is also related to the social values of taxpayers, which is related to the service provided by tax authorities to taxpayers, specifically in providing the ease of tax administration. With this article, hopefully, the tax authorities–especially in developing countries–will pay more attention to the important issue of tax literacy so that they can design efficient policies in an effort to increase tax compliance.